Pemberian Limbah Sayuran Tomat, Kubis dan Wortel Terhadap Kandungan Protein dan Lemak Larva Maggot/ Black Soldier Fly (Hermetia illucens) - Sigit, Miarsono; Aprilia, Zelvi (Universitas Islam Kadiri, 2023)
The aimed of study to know the content of protein and fat on the larvae of flies the Black Soldier Fly given the feed from different organic wastes (cabbage, tomatoes, carrots and mix all three). This type of research was a research experimental by a complete randomized design (RAL) with 4 treatments and 4 replicates. The fourth treatment is P1 (6 kg of waste a mixture of cabbage, tomatoes and carrots), P2 (6 kg waste cabbage), P3 (6 kg of tomato waste). P4 (6 kg waste carrots). This research was conducted for 12 days with the larva used 5 DOL. Data obtained were analyzed by Analysis of Variance (ANOVA) one way. The results showed a very real difference (P < 0.01) between the media mix, media cabbage, tomato and carrot media on larvae protein test flies the Black Soldier Fly (Hermetia illucens) with the highest average content of protein founded in medium tomatoes, namely in the amount of 11.4267%, where fat content test to indicate the absence of any real difference (P > 0.05) between the media mix, media cabbage, tomato and carrot media media with the highest average levels of fat founded in the media carrot that is of 0.9533%. There is the effect of feeding organic wasted (cabbage, tomatoes, and carrots) on protein content and fat content in the Black Soldier Fly larvae (Hermetia illucens).